Analisis Faktor-Faktor yang Mempengaruhi Nilai Tukar Petani Peternakan di Provinsi Aceh - Safitri, Nadia; Satia Negara Lubis; Rahmanta (Universitas Medan Area, 2026)
This study aims to analyze the factors that affect the exchange rate of farmers in the livestock subsector of Aceh Province using the Autoregressive Distributed Lag (ARDL) method. The variables used in the study are the decomposition of the components that make up the Livestock Farmer Exchange Rate, namely the price index paid by farmers for household consumption expenditure, seed prices, prices of medicines and feed, rent and other expenses, transportation costs, costs of adding capital goods, wages of farm workers and the exchange rate of livestock farmers for the period January 2017 to December 2024 obtained from the Central Statistics Agency. The results of the study show that in the long term, the variables of the household consumption price index, the rental price index and other expenses, the seed price index and the labor wage price index have a significant effect on the exchange rate of livestock farmers in Aceh Province, while the variables of the drug and feed price index, the transportation price index and the price index of capital goods addition do not have a significant effect. In the short term, the household consumption price index and the transportation price index have a significant effect on the exchange rate for livestock farmers in Aceh Province. In contrast, the variables of the seed price index, the price index of medicines and feed, the price index of rent and other expenses, the price index of capital goods, and the price index of labor wages do not have a significant effect. Keywords: Farmers' Exchange Rate of Livestock; Price Index Paid by Farmers; ARDL